Cultural imperialism in Philippine Television. - Paborada, Connie; Parcon, Jude Vincent (2005.)
Mass media in the Philippine setting has three roles, Political, Social and Economic. These roles have to be realized and financial capability is being put to question. That is why; lots of television networks have been importing foreign shows that cost less to gain much profit. with this influx of foreign programs in Philippine television there is a tendency that Philippine culture may be dominated by foreign cultures, such that cultural imperialism may develop., Is there cultural imperialism in Philippine television? To answer this problem, it is important to determine the following; The awareness of the Ilonggo audience of the existence of Asian telenovelas in Philippine television, the Ilonggo audience's level of perception and attitude towards Asian telenovelas, the level of influence of Asian telenovelas to the Ilonggo audience and to analyze of the various factors in relation to cultural imperialism in Philippine television. This study focuses on the possible influence of Asian telenovelas among the Ilonggo audience as represented by Mass Communications students from the University of Iloilo, Central Philippine University, St. Paul University and West Visayas State University. Using the Culutral Imperialism Theory, the researchers have used the survey method and the purposive ssampling design to gather data and later a descriptive and qualitative way was used to interpret the data. Results show that the Ilonggo audience is actually aware of the existence of Asian telenovelas since a majority of them watch these shows. Moreover, because of their exposure to these shows they are able to develop a likely favorable perception and attitude towards Asian telenovelas. Since they have a likely favorable attitude and perception, the influence towards them is also likely favorable, this as shown by the results. Considering the results, there is indeed cultural imperialism in Philippine television.
Research Project (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Philippine Television -- Cultural imperialism